RANCANG FILTER AUGMENTED REALITY INSTAGRAM UNTUK EDUKASI KESEHATAN MENTAL DI KALA PANDEMI - KAUSAD, JIHAN; RACHMAN, ANUNG; NURHADI, ASMORO (Institut Seni Indonesia Surakarta, 2022)
Excessive anxiety can worsen the mental health of citizens and result in a decrease in their productivity in living life. Therefore, this research was conducted to educate the public on how important it is to encourage and support one another to maintain mental health in the face of a pandemic by using Instagram's augmented reality filter. However, the effectiveness of mental health education using Instagram's augmented reality filter is still unknown. The purpose of making this Instagram augmented reality filter is to make it easier to educate the public and reach a wider audience. The design method used for this research is the design thinking method. In this method there are 5 stages, namely empathize, define, ideate, prototype, and test. The reason for using this method is because the stages are very appropriate in conducting this research. The results show that this filter can be accepted by the community and the majority say that this filter is quite interesting to use.